LITERASI SAMPAH LAUT BAGI SISWA SD KRISTEN REHOBOTH KECAMATAN NUSANIWE KOTA AMBON - Tuahatu, Juliana W.; Ratuluhain, Eva S.; Saleky, Valentine D.; D. Manuputty, Gratia; Noya, Yunita A. (HIRONO : Jurnal Pengabdian Masyarakat, 2026)
Marine debris is an environmental problem that has serious impacts on ecosystems, human health, and the social and economic aspects of coastal communities. Most marine debris originates from land-based activities carried by rivers to the sea, with plastic being the dominant component. Plastic debris is difficult to decompose, has the potential to become microplastics, and can pollute marine biota and enter the human food chain. The degradation of coastal ecosystems due to debris in the Maluku Islands is increasingly worrying, necessitating educational efforts through increasing marine debris literacy from an early age. A Community Service (PkM) activity by the Marine Science Study Program Team was carried out at Rehoboth Christian Elementary School, Ambon, with the aim of increasing students' knowledge and awareness of waste management based on the 3R principle. The implementation method included material socialization, interactive activities, and discussions. Participants were 45 students from grades I and II of Rehoboth Christian Elementary School, Ambon. The results of the activity showed enthusiasm and increased student understanding of the importance of protecting the marine environment, so it is hoped that they can play a role as agents of change in maintaining coastal cleanliness